Analisis Kesalahan Penggunaan Tanda Baca pada Proposal Penelitian Mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Riau - Novrila Z; Ermawati Sulaiman (UIR Press, 2022)
The background of this research is that there are still errors in the use of punctuation marks in research proposals by students of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Riau Islamic University. The method used in this research is content analysis. The data collection technique of this research is using hermeneutic techniques. Meanwhile, the data analysis techniques of this research are data identification, data classification, and conclusion. The results showed that the form of errors in the use of punctuation in the research proposals of students of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Islamic University of Riau amounted to 497 error cases, including 116 errors with a period (.) and a comma ( ,) totaling 226 errors, colon (:) totaling 46 errors, semicolon (;) totaling 11 errors, ellipsis (...) totaling 2 errors, parentheses ((...)) totaling 21 errors, single quotation marks ('...') totaled 9 errors, quotation marks (“...”) totaled 27 errors, question mark (?) totaled 1 error, exclamation mark (!) had 2 errors, and hyphen (- ) amounted to 36 errors.